Integrated ozone—electrocoagulation process for the removal of pollutant from industrial effluent: Optimization through response surface methodology - Asaithambi, P.; Abdul Raman, Abdul Aziz; Daud, Wan Mohd Ashri Wan (Elsevier, 2016)
In this study, the efficiency of ozonation, electrocoagulation and ozone assisted electrocoagulation processes for removal of pollutants from effluent of distillery industry was compared. The experimental results showed that ozone assisted electrocoagulation process yielded higher pollutant removal than ozone and electrocoagulation processes alone. Response surface methodology based on central composite design was used to optimize various operating parameters of the ozone assisted electrocoagulation process for the treatment of industrial effluent. The effects of five independent parameters such as current density(X1), COD concentration(X2), effluent pH(X3), inter-electrode distance(X4) and electrolysis time(X5) on the% COD removal and power consumption were investigated. A quadratic model was used to predict the COD removal and power consumption in different conditions. The significance of independent variables and their interaction were evaluated by ANOVA. In order to achieve the maximum COD removal and minimum power consumption, the optimum conditions were obtained by mathematical and statistical methods. The results showed that maximum COD removal efficiency could be achieved at optimum conditions of X1 − 3A/dm2, X2 − 3000 ppm, X3 − 7, X4 − 1.8 cm and X5 − 5 h. In conclusion, hybrid electrocoagulation process could be applied successfully for removing pollutants from effluent.